Basic welding for farm and ranch : essential tools and techniques for repairing and fabricating farm equipment - Galvery, William L., Jr.; Martindell, Michael (North Adams, MA : Storey Publishing, 2019)
"Master the fundamentals of welding, brazing, and soldering so you can repair equipment both big and small, from a garden rake to a mower. Learn to add a bale spear to your tractor bucket, build a wall-mount hay feeder, or make metal hooks. Real repair scenarios help you strategize for those moments when you need to fix equipment in bad weather, at awkward angles, or out in the field."--Back cover.
An overview of welding processes -- General tools, materials, and safety equipment -- Oxyacetylene welding -- Oxyacetylene cutting -- Shielded metal arc welding: arc welding and stick welding -- Wire feed welding processes: MIG welding and flux-cored arc welding -- Brazing and soldering -- Welding tasks and tips.
Includes index.
107423
Keywords: Welding; Farm equipment -- Maintenance and repair; Handbooks and manuals